Structure and properties of the (Cr, Al)N coatings deposited by PIII&D method - Vasyliev, V.V.; Luchaninov, A.A.; Reshetnyak, E.N.; Strel’nitskij, V.E.; Lorentz, B.; Reichert, S.; Zavaleyev, V.; Walkowicz, J.; Sawczak, M. (Вопросы атомной науки и техники, 2016)
Cr-Al-N coatings deposited from the vacuum-arc plasma source with rectilinear macroparticle filter were investigated. Influence of the amplitude of pulsed substrate bias potential in the range of 0…2500 V on the structure and mechanical properties of the coatings was studied. It is found that in all coatings formed solid solution of (Cr, Al)N with a cubic structure type NaCl. High voltage pulsed potential bias causes formation of the coatings structure with fine grains (6…7 nm) and strong axial texture [110]. Residual compressive stress varies nonmonotonously from 2 to 7 GPa when the amplitude of the pulses increases. The coatings are characterized by high hardness 30…36 GPa, the surface roughness at the level of 40…50 nm and a low friction coefficient, which allows their use as protective coatings for tools and friction units